AB1026 INFLAMMATORY MANIFESTATIONS IN PATIENTS WITH HUMAN LEUKOCYTE ANTIGEN-B*51 POSITIVE AND WITHOUT BEHÇET'S DISEASE. (2nd June 2020) - Duarte, M.; Sousa Morais, J.; Faria, R.; Guerra Leal, B.; Marinho, A.; Correia, J.; Farinha, F.; Pinho Costa, P.; Martins Da Silva, B.; Vasconcelos, C.
Abstract : Background: Human leukocyte antigen (HLA) B*51 allele is the most important genetic factor in susceptibility to Behçet's disease (BD), an immune-mediated systemic disorder of unknown etiology, characterized by recurrent episodes of inflammatory manifestations. In fact there is a considerable clinical overlap of BD with autoinflammatory syndromes. As it's known, the majority of HLA-B*51 positive individuals do not develop BD. But do these individuals also present inflammatory manifestations? Objectives: Characterize the group of individuals in our hospital with positive HLA-B*51, without BD diagnosis and review whether inflammatory manifestations are present in these individuals. Methods: A retrospective study of HLA-B*51 positive patients between 2000 and 2019. Genomic DNA was obtained from peripheral blood and HLA genotyping was performed using a PCR with Sequence Specific Primers (PCR–SSP) methodology. From the group of 289 B*51 positive patients, BD diagnosis were excluded. Demographic and clinical data were collected by review of clinical files in December 2019. Results: 176 patients, mean age of 48.5 ± 16.5 years (5 to 84 years). Most were female (68%). The HLA study was motivated by multiple diagnostic suspicions: spondyloarthritis (SpA, 25.0%), BD (22.7%) and systemic sclerosis (SSc, 10.8%). The mean time elapsed since the immunogenetic study was 8.3 years, with 12 deaths recorded. 69 (39.2%) subjects had no diagnosis for immune-mediated disease (IMD). Of the other 107 patients, the majority had 1 IMD (64.5%), and the rest were diagnosed with 2 to 4 IMD. The most frequent IMD were SpA (20.8%), psoriasis (10.4%), psoriatic arthritis (9.7%), SSc (9.7%) and rheumatoid arthritis (7.1%). Autoantibodies were detected in 94 individuals (53.4%): antinuclear antibodies (64 patients), rheumatoid factor (26 patients) and CCP antibodies (11 patients). In 55 individuals no inflammatory manifestation was identified but the 68.8% of them presented between 1 to 7 manifestations: Conclusion: Inflammatory manifestations are common in HLA-B*51 positive individuals, even in those without BD diagnosis. Further research is needed, considering other HLA alleles associated with increased risk of BD and including control groups. References: [1]Burillo-Sanz S, Montes-Cano M, García-Lozano J, et al . Behçet´s disease and genetic interactions between HLA-B*51 and variants in genes of autoinflammatory syndromes. Sci Rep 2019;9:2777. [2]McGonagle D, McDermott MF. A Proposed Classification on the Immunological Diseases. PLoS Med 2006;3(8):e297. [3]Tong B, Liu X, Xiao J, Su G. Immunopathogenesis of Behcet´s Disease. Front. Immunol 2019;10:665. Disclosure of Interests: None declared